2017
DOI: 10.1111/jam.13406
|View full text |Cite
|
Sign up to set email alerts
|

Growth, biogenic amine production andtyrDCtranscription ofEnterococcus faecalisin synthetic medium containing defined amino acid concentrations

Abstract: This study gives deeper insight into the metabolic regulation of tyrDC activity of enterococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…I.e., the catabolic genes tdcA, tdcP , and nhac-2 – that encode a tyrosine decarboxylase, a tyrosine-tyramine antiporter and a Na + /H + antiporter, respectively – are over-expressed by tyrosine, while the tyrS which encodes an aminoacyl-tRNA synthetase-like gene is repressed. This effect of tyrosine on tdc cluster expression has also been demonstrated in other E. faecalis strains by Bargossi et al (2015 , 2017 ).…”
Section: Discussionsupporting
confidence: 71%
“…I.e., the catabolic genes tdcA, tdcP , and nhac-2 – that encode a tyrosine decarboxylase, a tyrosine-tyramine antiporter and a Na + /H + antiporter, respectively – are over-expressed by tyrosine, while the tyrS which encodes an aminoacyl-tRNA synthetase-like gene is repressed. This effect of tyrosine on tdc cluster expression has also been demonstrated in other E. faecalis strains by Bargossi et al (2015 , 2017 ).…”
Section: Discussionsupporting
confidence: 71%
“…They investigated firstly the tyrosine effect on the tdc cluster transcription of E. faecalis by microarray experiment, highlighting, in the presence of tyrosine, an over-expression of tdcA , tdcP , and nhac-2 genes and a repression of tyrS . Bargossi et al [15,155] have also demonstrated the same effect in other E. faecalis strains. Moreover, Perez et al [154] showed that tyrosine induced putrescine biosynthesis genes, as confirmed by reverse transcription quantitative PCR (RT-qPCR) results.…”
Section: Main Lab Involved In Ba Production In Fermented Foodsmentioning
confidence: 61%
“…The presence of biogenic amines in food constitutes a potential public health concern because of their physiological and toxicological effect. At high concentrations, they are known to cause food poisoning, due to their vasoactive properties (Bargossi et al, 2017 ). The most dangerous are histamine (produced from histidine) and tyramine (produced from tyrosine) and are regarded as undesirable compounds that may cause health disruptions to sensitive consumers (EFSA Panel on Biological Hazards, 2011 ).…”
Section: Current Applications Of Enterococci and Their Bacteriocinsmentioning
confidence: 99%
“…Biogenic amines are mainly accumulated in foods through microbial decarboxylation of certain amino acids (Gardini et al, 2016 ). Enterococcus species, together with other lactic acid bacteria, constitutes one of the microorganisms that can accumulate higher biogenic amines; they are indeed known as the most efficient tyramine producers in fermented foods (Ladero et al, 2012 ; Bargossi et al, 2017 ; Laukova et al, 2017 ). Therefore, control measures to prevent biogenic amine formation in foods or to reduce their levels once formed must be taken.…”
Section: Current Applications Of Enterococci and Their Bacteriocinsmentioning
confidence: 99%